Parâmetros fitoquímicos, genotóxicos e de crescimento de alecrim em diferentes salinidades e doses de nitrogênio - Frescura, Viviane Dal Souto (2014)
Rosmarinus officinalis L., popularly known as rosemary, is a medicinal and aromatic species used in the cosmetics and food processing industries, with interest for the herbal industry. This study aimed to determine the biomass production and volatile oil during the growth of rosemary plants cultivated under different salinity (nutritious solution concentrations) and different nitrogen (N) concentrations, and to evaluate the effect of the extracts and volatile oil of the species on the Allium cepa L. cell cycle and genetic material, as well as knowing the phenolic compounds present in the extracts and the chemical composition of volatile oil. The work was divided into two stages: the first aimed evaluating the production of biomass and volatile oil during the rosemary plants growth cultivated under different nutritious solution concentrations, as well as the effect of oil and extracts on the A. cepa cell cycle and genetic material, besides determining the chemical composition of the oil and the phenolic compounds present in the extracts; the second stage aimed evaluating biomass and volatile oil production during the rosemary plants growth cultivated under different N concentrations, as well as the effect of oil and the extracts on the A. cepa cell cycle and genetic material, and determining the chemical composition of the oil and the phenolic compounds present in the extracts as well. The rosemary leaves were collected and analyzed for dry matter, volatile oil extraction and preparation of aqueous extracts by infusion at 5, 20, and 50 g.L-1 concentrations for plants cultivated under different salinities, and 5 and 50 g.L-1 concentrations for plants cultivated at different N concentrations. The volatile oil was analyzed by Gas Chromatography to knowledge of its constitution, and the aqueous extracts were analyzed by High Performance Liquid Chromatography for phenolic compounds determination. The oil and extracts effect was evaluated on the A. cepa cell cycle and genetic material. The completely randomized design was used, and the biomass production and volatile oil yield data were subjected to analysis of variance with polynomial regression and the remaining data were compared by the Scott-Knott test at the 5% level of probability. The nutritious solution concentration, the N concentration and the plant age interfere into the biomass production, and consequently into the rosemary volatile oil yield. However, do not alter the oil and extracts effect on the A. cepa cell cycle and genetic material. The volatile oil and extracts inhibited cell division in all concentrations, and this effect is dose-dependent. In addition, extracts did not show genotoxicity, in spite of oil concentration of 10% being genotoxic. The majority compounds camphor, 1.8 cineole, α-pinene, β-myrcene and verbenone, beyond of β-pinene compounds only controlling the oil crop plants in the concentrations of 8:05, 13:05 and 15:55 mmol.L-1. The phenolic compounds present in the extracts were rosmarinic acid, chlorogenic acid, caffeic acid, carnosic acid, kaempferol, quercetin and rutin.